The scientist and the serial killer: the search for houston's lost boys - Olsen, Lise (Random House, 2025)
"Houston, Texas, in the early 1970s was an exciting place to grow up. It was the home of NASA, the city of the future. But a string of missing teenage boys, all from the same neighborhood, spoke to a dark undercurrent that would go ignored for too long. While their siblings and friends wondered where they'd gone, the Houston Police Department dismissed them as runaways, fleeing the Vietnam draft or conservative parents, looking to get high or join the counterculture. It was only after their killer, Dean Corll, was murdered by an accomplice that the boys' bodies were discovered in several mass graves around Houston. Also known as the "Candy Man," Corll was a local sweet shop owner who had enlisted two teenage boys to lure their friends to parties where they would be tortured and killed, their bodies then dumped in mass graves around Houston. But many of Corll's victims, known collectively as the Lost Boys, had never been identified. Forty years later, when forensic anthropologist Sharon Derrick discovered a box of remains marked "1973 Murders" in the Harris County Morgue, she knew she had to bring these boys home. It would take prison interviews with Corll's accomplices, advanced scientific techniques, and years of tireless effort to identify the young men whose lives had been taken. But one by one, their names were returned to them. Veteran investigative journalist Lise Olsen immerses readers in this astonishing story, simultaneously bringing to life a suburban community hunted by a silent killer and the extraordinary woman who, decades later, would finally give his victims back their dignity"-- Provided by publisher